Changing the local coordination environment in mono- and bi- nuclear lanthanide complexes through "click" chemistry. - Jauregui, M; Perry, W; Allain, C; Vidler, L; Willis, M; Kenwright, A; Snaith, J; Stasiuk, G; Lowe, M; Faulkner, S (2009)
Alkyne appended lanthanide complexes derived from DO3A undergo copper catalysed cycloaddition reactions with azides to form triazole appended complexes: coordination of one of the triazole nitrogen atoms to the metal centre changes the local coordination environment and the spectroscopic properties of the complex.